Combination Strategy for the Geocentric Realization of Regional Epoch Reference Frames. Issue 10 (25th October 2022) - Kehm, A.; Sánchez, L.; Bloßfeld, M.; Seitz, M.; Drewes, H.; Angermann, D.; Seitz, F.
Abstract: For high‐resolution regional geodetic applications, the International Terrestrial Reference Frame (ITRF) is complemented by regional densifications. These are realized either as multi‐year solutions related to a tectonic plate (e.g., EUREF for Europe) or as epoch reference frames (ERFs) to capture nonlinear geophysical station motions caused by, for example, earthquakes or non‐tidal loading (e.g., SIRGAS for Latin America). These Global Navigation Satellite Systems (GNSS)‐only based regional reference frames have in common that their geodetic datum is aligned with the ITRF datum at a specific epoch. The consequence is that their origin represents the Earth's center of figure and does not coincide with the instantaneous center of mass. Here, we present studies on a direct geocentric realization of regional ERFs. We propose to realize the geodetic datum for each epoch by combining global GNSS, Satellite Laser Ranging, and Very Long Baseline Interferometry networks via measured local ties at co‐located sites. A uniformly distributed global GNSS network is used to realize the orientation via a no‐net‐rotation constraint with respect to the ITRF and is densified by the stations of the regional subnetwork. The developed combination and filtering strategy aims to guarantee a stable datum realization for each epoch‐wise solution. Validating our results against global reference frames and geophysical loading models relating to the Earth's centers of mass and figure, we show that the realized displacement time series are geocentric and reflect seasonal geophysical processes. As the approach does not need to rely on co‐location sites in the region of interest, it is conceptually transferable to other regions on the globe. Plain Language Summary: In today's world, precise ground, sea, and air navigation and the accurate monitoring of geophysical processes are vital. Precise coordinate reference frames make it possible to relate observed displacements to the Earth system. For different regions, these reference frames are materialized by dense networks of Global Navigation Satellite Systems (GNSS) stations with precisely determined position coordinates. It is crucial that the origin (defined to coincide with the Earth's center of mass), the scale (the realized unit of length), and the orientation (with respect to the Earth's crust) of the reference frame match their conventional definition. The realization of this so‐called "geodetic datum" for current conventional reference frames suffers from several deficiencies. We have developed a strategy for the precise weekly geocentric realization of regional reference frames. Coping with the changing and inhomogeneous distribution of stations by observing different space‐geodetic techniques, we developed and implemented a strategy to improve the long‐term stability of the solutions. We show that this approach allows for monitoring geophysical processes (loading and earthquakes) at low latency and overcomes the problems of existing realizations. The developed strategy is based on global networks and its effectiveness is demonstrated in Latin America; however, it can be applied to any region of the Earth. Key Points: Geocentric datum realization for regional epoch reference frames Combination of space‐geodetic techniques at normal equation level Long‐term stability of the geocentric datum stability by a filtering approach